(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of the competent implementation of pedagogical technologies by the teacher, also describes the concept of pedagogical assessment and describes the importance of its application, in the context of democratization of the educational process. The difference between the score and the mark is highlighted. A brief description is given of the styles of pedagogical communication, where the democratic style acts as the most favorable for teaching. Also, a characteristic of psychological features of 11 children of secondary school period is given. This work is supported by a study on the impact of the mark on the child and brief results on it.